The effect of the information technology application and professional ethics on auditors performance - Mulia Saputra; Mia Lutfi Shara (Proceedings of AICS - Social Sciences, 2017)
This study aims to determine the effect of the information technology application and professional ethics on the auditor's performance. The population of this study was all auditors working at the BPK RI Office of Aceh Province represented 87 auditors. Stratified random sampling multiple regression analysis models are applied in this study. This research is Causal Study. The results indicate that information technology application and professional ethics simultaneously affect the performance of BPK RI Representative of Aceh Province. Information technology application and professional ethics have a positive effect on auditor performance Audit Board of Republic of Indonesia Representative of Aceh Province.